Sistematika fasadnih oblog - Zbašnik-Senegačnik, Martina (AR. Arhitektura, raziskave, 2004)
The facade cladding performs a significant function in the composition of the facade cover. First of all it protects a building's outer wall from external environmental effects, since it contains temperature burdens and protects lower layers from wind, bad weather, fire etc. To perform these protective functions it has to have good mechanical robustness, resistance to temperature changes and good adhesiveness to the structure, when it lies tightly against the wall, etc. Besides such protective function, the facade cover also has strong design implications, which are given by type of material, form of facade cladding elements,texture, colour but also method of fastening to the carrying wall. In the article facade claddding is systemised into basic groups of materials; also shown are different mrethods of fastening, their technical characteristics, properties of various systems, possibilities for use and reference buildings.
Keywords: zgradbe; fasade; fasadne obloge; fasadni ovoji